If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5m + 11(12 + 7m) = 5m + -8(-6m + -2) 5m + (12 * 11 + 7m * 11) = 5m + -8(-6m + -2) 5m + (132 + 77m) = 5m + -8(-6m + -2) Reorder the terms: 132 + 5m + 77m = 5m + -8(-6m + -2) Combine like terms: 5m + 77m = 82m 132 + 82m = 5m + -8(-6m + -2) Reorder the terms: 132 + 82m = 5m + -8(-2 + -6m) 132 + 82m = 5m + (-2 * -8 + -6m * -8) 132 + 82m = 5m + (16 + 48m) Reorder the terms: 132 + 82m = 16 + 5m + 48m Combine like terms: 5m + 48m = 53m 132 + 82m = 16 + 53m Solving 132 + 82m = 16 + 53m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-53m' to each side of the equation. 132 + 82m + -53m = 16 + 53m + -53m Combine like terms: 82m + -53m = 29m 132 + 29m = 16 + 53m + -53m Combine like terms: 53m + -53m = 0 132 + 29m = 16 + 0 132 + 29m = 16 Add '-132' to each side of the equation. 132 + -132 + 29m = 16 + -132 Combine like terms: 132 + -132 = 0 0 + 29m = 16 + -132 29m = 16 + -132 Combine like terms: 16 + -132 = -116 29m = -116 Divide each side by '29'. m = -4 Simplifying m = -4
| s^2-19s=-88 | | 3m/5-3/20 | | -4y+x+z=6 | | r(b-3)+t(b-3)= | | 18=15+a | | 29=13+b | | 4(b-2)=2(5-6) | | 0.02q+2.1r=3.16-.2r | | -2(x-4)=3x+7 | | 16x^2-10x^2+8x=0 | | 18-m=16 | | 5p-6p=1 | | 5r+4s= | | 10(6x-2)=+4(12x+6) | | s^2-19s+88=0 | | (2x+5)+(5x-7)=18 | | 1/4x=1/4x | | 6=-5a+4a | | 31-4(2x+11)=19 | | 3+3x+3=x-1 | | .74(x-12)=12 | | b-4=-4-4b | | 2m+6+4m=-6 | | ln(2x+1)(x+2)=2ln(x+2) | | 11x-2(3x+7)=6 | | -10d=4 | | 4x-4/5x=64 | | 2x^2/7*3/4x^2 | | 10x-3=45x+4 | | w^2-11w-110=-110 | | -15=-6m-3+2m | | X^2-33x-240=0 |